How to comply with Sarbanes-Oxley Section 404 : assessing the effectiveness of internal control - Ramos, Michael J. (Finance professional collection, 2008)
How to Comply with Sarbanes Oxley Section 404: Assessing the Effectiveness of Internal Control, 3E, provides a comprehensive, structured approach for the testing and evaluation of internal control. Now in its third edition, this book was the first and con.